Today's Relevance of the Development of Information – Intellectual Skills Through the Teaching of Students on the Basis of Modern Approaches (Eurasian Scientific Herald, 2022)
The article focuses on the interrelationships of components such as mastery, fragmentation, repetition and consolidation for modern lessons, acquisition of new learning material and control of previously learned in relation to its practical application. answers to questions such as what education is, the difference between traditional education and modern education